2020
DOI: 10.2147/rmhp.s247686
|View full text |Cite
|
Sign up to set email alerts
|

<p>Drug-Related Problems and Pharmacist Intervention at a General Hospital in the Jazan Region, Saudi Arabia</p>

Abstract: Patients and Methods: This retrospective study was conducted among inpatients at Ministry of Health hospital in Jazan, a region in southwestern Saudi Arabia. We collected data for a 2-year period (from 2016 to 2017). For any detected DRP of the ordered medications for dispensing, the inpatient pharmacist is sending report for that particular DRP with recommendation to the medical team which in turn might accept or reject such recommendation. Serious drug-drug interactions, as part of DRP, were assessed by util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
2
15
0
Order By: Relevance
“…Our results showed that antibiotics (16.8 %) were the most common drug classes associated with interventions, which goes hand on hand with previous studies ( Wang et al, 2021 , Faqeer et al, 2021 , Babelghaith et al, 2020 May , Hajjar et al, 2021 ). This was followed by electrolytes/minerals (11.7 %) and vitamins (9.4 %).…”
Section: Discussionsupporting
confidence: 80%
“…Our results showed that antibiotics (16.8 %) were the most common drug classes associated with interventions, which goes hand on hand with previous studies ( Wang et al, 2021 , Faqeer et al, 2021 , Babelghaith et al, 2020 May , Hajjar et al, 2021 ). This was followed by electrolytes/minerals (11.7 %) and vitamins (9.4 %).…”
Section: Discussionsupporting
confidence: 80%
“…They are common among people living with chronic illness like diabetic patients [ 9 ]. If drug therapy problems are not addressed, they can lead to clinical complications [ 21 ]. Detecting and resolving DRPs is important to ensure that patients achieve the optimal therapeutic goals [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Saudi Arabia, DRPs are common in different wards. [11][12][13] Rashed et al 14 reported a relatively high incidence 51.1% of DRP in pediatric wards, and wrong dose was the most common DRP. More than a quarter 27.0% of errors were clinically moderate and most of them 80.3% were preventable.…”
Section: Introductionmentioning
confidence: 99%